(untitled) - Scheffer, Victor B. (New York, 1969)
A rare and timeless book that takes the reader beneath the ocean's surface to travel with a young sperm whale. With a new foreword by the author. "A writer of unusual grace and feeling ... This is a fine book".
Keywords: Sperm whale,Tinh trùng cá voi